Materials for the Flora of Mt. Abu in Rajasthan - Jain, S. K. (Indian Forester, 1962)
Mt. Abu on south-western end of the Aravallis is the highest hill (alt. 1,722 m.) in Rajasthan. It is the solitary spot of this altitude in the wide gap between the Himalayas and the hill ranges of Deccan, the Western Ghats. The flora, therefore, is of great phytogeographical significance. The geology and climate of the place has been briefly described. A review of previous botanical work on this area has been given. A list of 469 species is given in the paper. It is based on previous reports and authors collections from the area during 1956-1960. 67 species have been reported from Mt. Abu for the first time.